Validation of Simulated Statistical Characteristics of Magnetosphere‐Ionosphere Coupling in Global Geospace Simulations Over an Entire Carrington Rotation - Qianfeng Yin; Kevin H. Pham; Junjie Chen; Binzheng Zhang (Space Weather)
Abstract We study the statistical features of magnetosphere‐ionosphere (M‐I) coupling using a two‐way M‐I model, the GT configuration of the Multiscale Atmosphere Geospace Environment (MAGE) model. The M‐I coupling characteristics, such as field‐aligned current, polar cap potential, ionospheric Joule heating, and downward Alfvénic Poynting flux, are binned according to the interplanetary magnetic field clock angles over an entire Carrington Rotation event between 20 March and 16 April 2008. The MAGE model simulates similar distributions of field‐aligned currents compared to empirical Weimer/AMPS models and Iridium observations and reproduces the Region 0 current system. The simulated convection potential agrees well with the Weimer empirical model and displays consistent two‐cell patterns with SuperDARN observations, which benefit from more extensive data sets. The Joule heating structure in MAGE is generally consistent with both empirical Cosgrove and Weimer models. Moreover, our model reproduces Joule heating enhancements in the cusp region, as presented in the Cosgrove model and observations. The distribution of the simulated Alfvénic Poynting flux is consistent with that observed by the FAST satellite in the dispersive Alfvén wave regime. These M‐I coupling characteristics are also binned by the Kp indices, indicating that the Kp dependence of these patterns in the M‐I model is more effective than the empirical models within the Carrington Rotation. Furthermore, the MAGE simulation exhibits an improved M‐I current‐voltage relation that closely resembles the Weimer model, suggesting that the updated global model is significantly improved in terms of M‐I coupling.